2015
DOI: 10.3727/096504015x14267282610858
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cellular Proliferation and Invasion by HMGB1 Knockdown in Bladder Urothelial Carcinoma Cells

Abstract: HMGB1, which acts as a DNA chaperone to help maintain nuclear homeostasis, was reported to play a prominent role in cancer progression, angiogenesis, invasion, and metastasis development. Increased expression of HMGB1 has been observed in several tumor entities. However, the molecular mechanisms of HMGB1 in tumorigenesis of bladder cancer have rarely been reported. In the present study, real-time quantitative RT-PCR analysis revealed that the expression of HMGB1 in human bladder urothelial carcinoma (BUC) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Radiation therapy can preserve urinary and sexual function and predict a high quality of life in patients 104. Liao et al105 showed that a decreased level of HMGB1-induced autophagy in bladder urothelial carcinoma (BUC) cells significantly inhibited the viability of BUC cells. Shrivastava et al106 reported the important role of HMGB1 as a predictive marker in bladder cancers subjected to radiation therapy and its correlation with autophagy.…”
Section: The Mechanism Of Hmgb1-induced Autophagymentioning
confidence: 99%
“…Radiation therapy can preserve urinary and sexual function and predict a high quality of life in patients 104. Liao et al105 showed that a decreased level of HMGB1-induced autophagy in bladder urothelial carcinoma (BUC) cells significantly inhibited the viability of BUC cells. Shrivastava et al106 reported the important role of HMGB1 as a predictive marker in bladder cancers subjected to radiation therapy and its correlation with autophagy.…”
Section: The Mechanism Of Hmgb1-induced Autophagymentioning
confidence: 99%
“…HMGB1 also functions as an inducer of EMT in human cancer cells (27)(28)(29)(30)(31). HMGB1 expression was much higher in bladder cancer cells than normal urethra epithelial cells and was associated with cell invasion (32,33). However, the mechanism of HMGB1 in bladder cancer is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of HMGB1 is correlated with progression of human cutaneous melanoma and poor patient survival (21). Knockdown or knockout of HMGB1 greatly inhibited proliferation, invasion, and cell cycle G 1 /S transition of bladder urothelial carcinoma cells (22). The aim of this study was to elucidate the potential roles of caspase-3 and caspase-8 in HCT-mediated apoptosis and to dissect the mechanisms that regulate HMGB1 release in a malignant melanoma cell line.…”
mentioning
confidence: 99%